A REVIEW OF THE PROTECTION OF INDONESIAN CITIZENS OF INDONESIA WHO ARE EXPOSED TO CASES OF PILGRIMAGE VISA ABUSE IN SAUDI ARABIA - Putri Rizkiyah, Salma; Ayad, Nahid (Universitas Negeri Surabaya, 2025)
The high number of unemployed and the lack of available jobs in the country have caused the number ofIndonesian Migrant Workers to increase every year. However, the large number of Indonesian MigrantWorkers still many of them do not fulfill the departure documents as stated in Article 13 of Law No. 18 of 2017 concerning the Protection of Migrant Workers, but in this article there is no explanationregarding sanctions or punishments if these documents are not owned by Indonesian migrant workers.This study discusses legal protection and efforts to repatriate Indonesian citizens who are involved incases of misuse of Pilgrimage Visas in Saudi Arabia. Researchers use normative legal research and astatutory approach, a case approach and a conceptual approach. Indonesian Labor Law has not yetregulated further regarding the legal protection that will be obtained by workers who depart illegally.The government provides a rehabilitation and reintegration program after the repatriation of Indonesian citizens involved in cases of misuse of pilgrimage visas and the government has also made several efforts to prevent similar cases from occurring.